Thermo-Responsive Polyurethane Hydrogels Based on Poly(ε-caprolactone) Diol and Amphiphilic Polylactide-Poly(Ethylene Glycol) Block Copolymers - Hsu, Shan-hui (Polymers (Basel), 2016)
Waterborne polyurethane (PU) based on poly(ε-caprolactone) (PCL) diol and an amphiphilic polylactide-poly(ethylene glycol) (PLA-PEG) diblock copolymer was synthesized. The molar ratio of PCL/PLA-PEG was 9:1 with different PLA chain lengths. The PU nanoparticles were characterized by dynamic light scattering (DLS), small angle X-ray scattering (SAXS) and rheological analysis. The water contact angle measurement, infrared spectroscopy, wide angle X-ray scattering (WAXS), thermal and mechanical analyses were conducted on PU films. Significant changes in physio-chemical properties were observed for PUs containing 10 mol % of amphiphilic blocks. The water contact angle was reduced to 12°–13°, and the degree of crystallinity was 5%–10%. The PU dispersions underwent sol-gel transition upon the temperature rise to 37 °C. The gelation time increased as the PLA chain length increased. In addition, the fractal dimension of each gel was close to that of a percolation cluster. Moreover, PU4 with a solid content of 26% could support the proliferation of human mesenchymal stem cells (hMSCs). Therefore, thermo-responsive hydrogels with tunable properties are promising injectable materials for cell or drug delivery.